Effects of bacterial fertilizer and green manure on soil enzyme activity and root characteristics in Korla fragrant pear orchard - He, Zhanyi; Li, Jie; Yang, Lele; Yan, Linsen; Chen, Bolang; Shen, Xing; Chai, Zhongping (Frontiers in Microbiology, 2025)
IntroductionIn arid regions, soil degradation and nutrient scarcity limit the productivity of Korla fragrant pear (Pyrus bretschneideri Rehd.). This study aimed to systematically evaluate how bacterial fertilizer and different green manures affect rhizosphere ecological functions and yield formation.MethodsA field experiment was conducted in a Korla pear orchard with six treatments: bacterial fertilizer (JF), two planting densities of sweet clover (CMX1, CMX2), two planting densities of oil sunflower (DK1, DK2), and a control (CK). Soil physicochemical properties, enzyme activities, root architecture, and yield were analyzed.ResultsBoth bacterial fertilizer and green manures significantly reduced soil pH and EC, improved nutrient content, and enhanced enzyme activity. Bacterial fertilizer was more effective in boosting enzyme activity, while sweet clover excelled in improving soil properties. Low-density green manures outperformed high-density ones. Root activity, vessel area, and yield were significantly increased by all amendments, with bacterial fertilizer showing the strongest effect. PLS-SEM analysis identified root activity as a key mediator linking soil improvements to yield gains.DiscussionThese results highlight the critical role of root activity in translating soil amendments into yield benefits. Among all treatments, low-density sweet clover (CMX1) offers the most cost-effective and sustainable strategy for improving soil fertility and pear yield in arid orchards.